A Severe Diabetic Foot Ulcer With Intermediate Cuneiform Displacement and Multidrug-Resistant Pseudomonas aeruginosa Infection: A Rare Case Report - Chai, Wei; Wang, Yuqing; Jiao, Fengjuan; Wu, Yili; Wang, Shuai (Frontiers in Medicine, 2020)
Diabetic foot ulcer (DFU) is considered as one of the most serious and prevailing complications of diabetes mellitus, while it is the major cause of amputations in diabetic patients. Herein, we reported an acquired severe traumatic DFU with an intermediate cuneiform hairline fracture and displacement in a 55-year old male (Grade IV of Wagner classification; Grade III of IWGDF classification). The Pseudomonas aeruginosa was identified in pus culture. Data of antibiotic susceptibility testing indicated that the isolates of Pseudomonas aeruginosa were multi-drug resistant. Routine debridement, clearing displaced intermediate cuneiform and drainage were performed to facilitate the outflow of pus and pressure mitigation. Dressing with Prontosan solution and gel was applied to the wound, and meropenem was systemically administrated in addition to effective glycaemic control. The DFU has been fully healed after approximately 40-day treatment. For this case, clearing the displaced and fractured intermediate cuneiform is essential for the heal of the DFU in addition to the common strategy for DFU treatment, i.e., the combination of debridement, pressure mitigation, wound dressing with Prontosan, antibiotic selection and effective glycaemic control. This case report might have value for the treatment of complex DFU with bone fracture and displacement, reducing the risk of amputation.